Target Situation in Vocational High School Civil Engineering Students’ Needs Analysis - Martina, Wigati; Astuti, Puji; Bharati, Dwi Anggani Linggar (English Education Journal, 2021)
Needs analysis for vocational high school English course is important because English course for vocational high school is considered too general compared to the target situation that the students will need in their future career. This study aimed to analyse the students’ teachers’, alumni’s, stakeholders’, and expert’s perceptions to explain the vocational high school civil engineering students’ needs in their English course. This study used a qualitative case design by using open questionnaires and in-depth interviews as the methods of collecting data. The findings showed that the main goal of the English course was to prepare the students to face the needs of English in their target situation. The learning approach needed was a scientific approach by using inquiry or discovery learning. The students needed more learning source which involved the target situation and a course which considered their current English proficiency. Finally, the students needed a course set that represented the target situation and teachers who were not only experts in pedagogical competence but also ESP. The results of the study can be used by the education practitioners to help them design better course for vocational high school civil engineering students.